Severe Obesity Is Associated with Symptomatic Presentation, Higher Parathyroid Hormone Levels, and Increased Gland Weight in Primary Hyperparathyroidism - Adam, Mohamed Abdelgadir (The Endocrine Society, 2010)
Context: A relationship between primary hyperparathyroidism (PHPT) and obesity has been observed but is incompletely understood. Furthermore, obesity has been associated with vitamin D deficiency, suggesting that the three conditions may be linked. Objective: We hypothesized that PHPT in morbidly obese patients is more severe and that the difference may be explained by vitamin D deficiency. Design and Setting, Participants, and Outcome Measures: Records of 196 patients with surgically treated PHPT and known body mass index (BMI) were examined. Patients were stratified into three BMI groups: group I (nonobese), BMI < 25 kg/m(2) (n = 54); group II (non-severely obese), BMI 25–34 kg/m(2) (n = 102); and group III (severely obese), BMI 35 kg/m(2) or greater (n = 40). Results: Preoperative PTH levels were higher in group ΙΙΙ compared with group Ι (181 ± 153 vs. 140 ± 80 pg/ml, p = 0.04). Group III patients had larger tumors on average compared with group I (1.8 ± 1.5 vs. 1.04 ± 1.5 g, P = 0.0002). In group III, BMI positively correlated with parathyroid tumor weight (r = 0.5, P = 0.002). Postoperative PTH was higher in group III compared with group Ι (61 ± 41 vs. 44 ± 28 pg/ml, P = 0.02). There was higher frequency of depression, musculoskeletal symptoms, weakness, and gastroesophageal reflux disease in group III patients. Conclusions: BMI positively correlated with parathyroid tumor weight independent of vitamin D. Severely obese patients have larger parathyroid tumor weight, higher pre- and postoperative PTH, and greater symptoms.